2021
DOI: 10.1371/journal.ppat.1009253
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the interactions between Blastocystis, the gut microbiota, and host immunity

Abstract: The human gut microbiota is a diverse and complex ecosystem that is involved in beneficial physiological functions as well as disease pathogenesis. Blastocystis is a common protistan parasite and is increasingly recognized as an important component of the gut microbiota. The correlations between Blastocystis and other communities of intestinal microbiota have been investigated, and, to a lesser extent, the role of this parasite in maintaining the host immunological homeostasis. Despite recent studies suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 99 publications
1
98
2
6
Order By: Relevance
“…Blastocystis sp. is one of the most common protists colonizing/infecting the gastrointestinal tract of humans and numerous animals and has a global distribution [ 1 , 2 , 3 , 4 ]. The pathogenicity of Blastocystis is controversial, as the presence of Blastocystis in humans has been associated with gastrointestinal symptoms and/or urticaria, but it is also commonly found in asymptomatic individuals [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blastocystis sp. is one of the most common protists colonizing/infecting the gastrointestinal tract of humans and numerous animals and has a global distribution [ 1 , 2 , 3 , 4 ]. The pathogenicity of Blastocystis is controversial, as the presence of Blastocystis in humans has been associated with gastrointestinal symptoms and/or urticaria, but it is also commonly found in asymptomatic individuals [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of Blastocystis is controversial, as the presence of Blastocystis in humans has been associated with gastrointestinal symptoms and/or urticaria, but it is also commonly found in asymptomatic individuals [ 5 , 6 , 7 ]. It has also been suggested that Blastocystis colonization could be associated with a healthy gut microbiome [ 4 ]. Blastocystis transmission is via the fecal-oral route, with direct transmission through contact with infected humans/animals or indirect transmission through ingestion of contaminated food and water [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The positive perception of its function, including its use as probiotic [ 45 ], is in contrast to the here observed inverse association with Blastocystis , an organism now gradually recognized as beneficial to the gut health (e.g. [ 46 ]). Interestingly, in a mouse model, a pathogenic ST7 decreased the abundance of two taxa beneficial for gut health, Bifidobacterium sp.…”
Section: Discussionmentioning
confidence: 76%
“…Some major contributors to this debate include the influences of co-infections, microbiome, and subtype identity of Blastocystis spp. (Deng et al, 2021 ). In one study presented in the Research Topic by Betts et al , the subtype identity of Blastocystis spp., concurrence of Cryptosporidium spp., Eimeria spp., Isospora spp., Entamoeba spp., and Giardia spp.…”
Section: Blastocystismentioning
confidence: 99%